Building Orientation On Traditional Balinese Culture - I Gusti Bagus Wijaya Kusuma (Humaniora, 2003)
Traditional Balinese reasoning of zoning area follows the physics of microcosms (bhuwana alit) and macrocosms (bhuwana agung). According to four palm leaf manuscripts (named Lontar) the Asta Kosala, Asta Kosali, Asta Patali and Swakarman [anonymous], the housing area is divided into nine regions. The region is then named into three sub-areas called nista, madya and utama (poverty, middle, and primary areas, respectively). In traditional Balinese architecture, people follow the hulu and teben (upward and downward directions, respectively). Upwards and downwards directions are defined following the movement of the sun or the mount - sea direction. Sunrise is upward and sunset is downward, or the mount is upwards and the sea is downwards. The Balinese make a clear differentiation between the dwellinggrounds and the unlived parts of the village, those for public use such as temples, assembly halls and market. The village is a unified organism in which every individual is a body and every institution is an organ. The heart of the village is the central square, invariably located in the center of the village, at the intersection of the two main avenues. Consequently, the crossroads are the center of a rose of the winds formed by the entire village, the cardinal directions mean a great deal to the Balinese and the crossroads are a magic spot of great importance [Covarrubias, 1972].